2021
DOI: 10.1371/journal.pone.0258098
|View full text |Cite
|
Sign up to set email alerts
|

Themes, communities and influencers of online probiotics chatter: A retrospective analysis from 2009-2017

Abstract: We build on recent examinations questioning the quality of online information about probiotic products by studying the themes of content, detecting virtual communities and identifying key influencers in social media using data science techniques. We conducted topic modelling (n = 36,715 tweets) and longitudinal social network analysis (n = 17,834 tweets) of probiotic chatter on Twitter from 2009–17. We used Latent Dirichlet Allocation (LDA) to build the topic models and network analysis tool Gephi for building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Goodman et al reviewed 42 RCTs of 26 different probiotics, concluding that L casei probiotics were “effective to prevent AAD,” but a closer examination of their data revealed that, of 5 different strains of Lacticaseibacillus (formerly Lactobacillus ) casei studied, only 1 (a 3-strain blend of L acidophilus CL1285, L casei LBC80R, and L rhamnosus CLR2) prevented AAD, whereas the other 4 were ineffective. This type of imprecision continues to occur in the published literature, despite being firmly discouraged …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Goodman et al reviewed 42 RCTs of 26 different probiotics, concluding that L casei probiotics were “effective to prevent AAD,” but a closer examination of their data revealed that, of 5 different strains of Lacticaseibacillus (formerly Lactobacillus ) casei studied, only 1 (a 3-strain blend of L acidophilus CL1285, L casei LBC80R, and L rhamnosus CLR2) prevented AAD, whereas the other 4 were ineffective. This type of imprecision continues to occur in the published literature, despite being firmly discouraged …”
Section: Resultsmentioning
confidence: 99%
“…This type of imprecision continues to occur in the published literature, despite being firmly discouraged. 25,31 When MAs were limited to 1 probiotic strain or used subgroups comprising identical strains (or the same strains in multistrain blends), it was possible to discern which strains might be effective for a given disorder. 35,39,47,50,[52][53][54]56,65 For example, Farahmandi et al 66 reviewed 13 RCTs for allergic rhinitis and found that conclusions could only be drawn on 2 of the 9 strains eligible for analysis (ie, among strains for immune marker responses.…”
Section: Pooling Data From Identical or Different Probiotic Strainsmentioning
confidence: 99%
See 1 more Smart Citation